Failure of thrombolysis: experience with a policy of early angiography and rescue angioplasty for electrocardiographic evidence of failed thrombolysis. Issue 2 (1st August 2000) - Sutton, A G C; Campbell, P G; Grech, E D; Price, D J A; Davies, A; Hall, J A; Stewart, M J; de Belder, M A
Abstract : OBJECTIVE: To assess the outcome of a policy of emergency coronary angiography with or without rescue angioplasty in patients with acute myocardial infarction and ECG evidence of failed reperfusion after thrombolysis. DESIGN: A cohort study. SETTING: Regional cardiothoracic unit. PATIENTS: 197 patients with acute myocardial infarction fulfilling a simple ECG criterion of failed reperfusion. INTERVENTIONS: Emergency coronary angiography proceeding to rescue angioplasty for inadequate antegrade flow. MAIN OUTCOME MEASURES: Hospital mortality for all 197 patients; incidence of successful and failed rescue angioplasty; need for additional revascularisation in those receiving rescue angioplasty compared with those not treated in this way. RESULTS: 197 patients had emergency angiography for ECG evidence of failed reperfusion; 156 patients received immediate rescue angioplasty. Overall hospital mortality for those undergoing rescue angioplasty was 11.5%. Rescue angioplasty achieved TIMI 2 (11) or TIMI 3 (124) in 135 patients, who had a hospital mortality of 5.9%. Failure to achieve at least TIMI 2 flow following rescue angioplasty occurred in 21 patients, with a hospital mortality of 48%. In the 41 patients in whom immediate rescue angioplasty was not performed, reinfarction or requirement for revascularisation occurred in 37%. Reinfarction occurred in three patients (1.9%) who had immediate rescue angioplasty. Hospital mortality for the whole cohort was 10.7%. CONCLUSIONS: A policy of emergency coronary angiography proceeding to rescue angioplasty where appropriate reduces mortality in a high risk group to a level less than expected for patients with acute myocardial infarction and ECG evidence of failed reperfusion. Unsuccessful rescue angioplasty is associated with a high mortality.